2020
DOI: 10.1016/j.buildenv.2019.106426
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation rates in California classrooms: Why many recent HVAC retrofits are not delivering sufficient ventilation

Abstract: Previous research has shown that under-ventilation of classrooms is common and negatively impacts student health and learning. To advance understanding of contributing factors, this study visited 104 classrooms from 11 schools that had recently been retrofitted with new heating, ventilation, and air-conditioning (HVAC) units. CO2 concentration, room and supply air temperature and relative humidity, and door opening were measured for four weeks in each classroom. Field inspections identified HVAC equipment, fan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…A review of the literature summarized studies in classrooms across North America, Europe, and Asia and found widespread evidence of inadequate ventilation [116]. Notably, many classrooms with recently retrofitted HVAC systems still had inadequate ventilation (especially those with wall-mounted units), often related to filters needing to be changed, disuse of the fan during the time the classroom was in use, or improper installation [117].…”
Section: Ventilationmentioning
confidence: 99%
“…A review of the literature summarized studies in classrooms across North America, Europe, and Asia and found widespread evidence of inadequate ventilation [116]. Notably, many classrooms with recently retrofitted HVAC systems still had inadequate ventilation (especially those with wall-mounted units), often related to filters needing to be changed, disuse of the fan during the time the classroom was in use, or improper installation [117].…”
Section: Ventilationmentioning
confidence: 99%
“…Conditions of vulnerability are especially pronounced in pre-schools and primary schools [45,46], due to the age of the potential students: 4 to 6 years of age in the former and 6 to 12 in the latter. Avoiding crowded, poorly ventilated classrooms is a requirement for the safe and healthy return of most pupils to school [29,47]. The implementation of a system of hygrothermal conditions and IAQ monitoring (air temperature (ta), RH, CO 2 ), together with other interventions, is conditional on the success of not exceeding acceptable limits [24].…”
Section: Introductionmentioning
confidence: 99%
“…The generally recommended maximum CO 2 concentration is 1000 ppm (Torpy et al, 2017;Lu et al, 2015;Tsai et al, 2012;Seppanen et al, 1999). Higher concentrations can have a negative effect on the people's performance in the indoor environment of buildings (Satish et al, 2012;Allen et al, 2016;Pinto et al, 2021;Chan et al, 2020). The sick building syndrome can appear in places with long-term occurrence in environments with higher concentrations of CO 2 .…”
Section: Description Of the Current Statementioning
confidence: 99%